Prevalence of Genital Mycotic Infections with Sodium-Glucose Co-Transporter 2 Inhibitors among Type 2 Diabetic Patients - Aslam, Sohail; Mehmood, Qaisar; Naeem, Nadeem; Das, Dial; Zafar, Qasim; Jamil, Hafsa (Indus Journal of Bioscience Research, 2025)
Background and Aim: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have emerged as an effective oral antidiabetic agents for glycemic control in patients with type 2 diabetes mellitus (T2DM). However, the mechanism of their action - promoting glycosuria - is associated with increasing risk of genital mycotic infections. The purpose of this study was to determine the prevalence of genital mycotic infections among T2DM patients using SGLT2 inhibitors. Patients and Method: A cross-sectional observational study investigated 300 T2DM patients receiving SGLT2 inhibitors in the Diabetes Management Center of Services Hospital, Lahore during January 16, 2025 to April 15, 2025. Clinical data, including the type and duration of demographic characteristics, SGLT2 inhibitors therapy, collected through structured interviews and medical records to the history of clinical data, HBA1C level, personal hygiene practices, and genital infections. The diagnosis of genital mycotic infection based on clinical symptoms and confirmed by laboratory findings where necessary. SPSS version 26 used for data analysis. Results: Of the 300 patients, 78 (26%) developed genital mycotic infections. The prevalence in women was much higher (38%) than men (17%) (p <0.01). Poor glycemic control (HBA1C> 8%) and inadequate hygiene important risk factor were found (P <0.05). The highest prevalence of was seen within the first 6 months of initiating SGLT2 inhibitor therapy, especially with dapagliflozin. 12 patients had recurrent infections, and most cases responded well to antifungal therapy without discontinuation of SGLT 2 obstructions.Conclusion: Genital mycotic infections have common but manageable side effects of SGLT2 inhibitors in T2DM patients, especially in women and those with poor glycemic control. Early patient’s education on genital hygiene and close monitoring can reduce the incidence and improve treatment adherence during the initial months of therapy.